An expanded access protocol of RT001 in amyotrophic lateral sclerosis—Initial experience with a lipid peroxidation inhibitor. Issue 4 (29th July 2022) - Yerton, Megan; Winter, Allison; Kostov, Anthony; Lieberman, Cassandra; Gelevski, Dario; Weber, Harli; Doyle, Michael; Kane, Geli; Parikh, Neil; Burke, Katherine M.; Rohrer, Margot; Stirrat, Taylor; et al.
Abstract: Introduction/Aims: Lipid peroxidation is thought to play a biologically important role in motor neuron death in amyotrophic lateral sclerosis (ALS). 11, 11 Di‐deuterated linoleic ethyl ester (RT001) prevents lipid peroxidation in cellular and mitochondrial membranes. Herein we report on the use of RT001 under expanded access (EA). Methods: We provided RT001 to patients with ALS via EA at a single site. The starting dose was 2.88 g/day, which was increased to to 8.64 g/day as tolerated. Participants were not eligible for alternative clinical trials. Participants were followed for adverse events and pharmacokinetic (PK) parameters were measured approximately 3 months after RT001 initiation. Results: Sixteen participants received RT001 (5.6 ± 1.6 g/day; dose range, 1.92 to 8.64 g/day) for a mean period of 10.8 ± 7.1 months. After 3 months of treatment, PK studies showed that RT001 was absorbed, metabolized, and incorporated into red blood cell membranes at concentrations expected to be therapeutic based on in vitro models. The most common adverse events were gastrointestinal, including diarrhea, which occurred in 25% of the participants, and were considered possibly related to RT001. One participant (6%) discontinued due to an adverse event. Ten serious adverse events occurred: these events were recognized complications of ALS and none were attributed to treatment with RT001. Discussion: RT001 was administered safely to a small group of people living with ALS in the context of an EA protocol. Currently, there is an ongoing randomized, double‐blind, controlled study of RT001 in ALS.